Synthesis of Soluble Novel Polyacetylenes Containing Carbamate and Eugenol Moieties - Erwin Abdul Rahim (Indonesian Journal of Chemistry, 2020)
This study was aimed to synthesize a series of novel polyacetylenes containing carbamate and eugenol moieties. The polymerization of 1-(3,4-dimethoxyphenyl) propane-2-yl prop-2-ynylcarbamate (1), 1-(3,4-dimethoxyphenyl)propane-2-yl 3-ethynyl phenylcarbamate (2), 1-(3,4-dimethoxyphenyl)propane-2-yl 4-ethynylphenylcarbamate (3), (2S)-1-(3,4-dimethoxyphenyl)propane-2-yl 2-((prop-2ynyloxy)carbonylamino)propanoate (4) in the presence of (nbd)Rh+[ɳ6-C6H5B–(C6H5)3] as catalyst have successfully produced corresponding polyacetylenes [poly(1)–poly(4)] in high yield. The molecular weight of the synthesized polyacetylenes ranged between 13,900–18,400 g/mol. In particular, the molecular weight of poly(1) could be increased by the addition of menthol. Practically, these polymers were found to have a stable helical structure and soluble in common organic solvents.